Using the modified Delphi technique to develop a framework for interprofessional education during international electives in health professions training institutions in Sub-Saharan Africa - Nawagi, Faith; Munabi, Ian Guyton; Vyt, Andre; Kiguli, Sarah; Rabin, Tracy; Waggie, Firdouza; Mubuuke, Aloysius Gonzaga (Frontiers in Medicine, 2023)
International electives provide a learning platform where interprofessional education and collaborative practice (IPECP) skills can be cultivated. However, hardly any frameworks to guide the implementation of interprofessional education (IPE) during international electives, especially in the context of low-income settings have been published. To address this gap, this study used the modified Delphi approach to develop an IPE framework guide for international electives to be used by health professions training institutions in Sub-Saharan Africa.A rapid literature review and a study among students and faculty in four African health professional training institutions were done to inform the process. This was followed by the modified Delphi technique that used three Delphi rounds with a panel of eight experts to build consensus on the final framework for IPE during international electives. The level of consensus was set at ≥70% on each of the statements in all rounds.Out of the 52 statements in round 1, (n=37, 71%) reached consensus while (n=15, 29%) of the statements did not reach consensus and were discussed in round 2. Round 2 led to 42 statements to be utilized for round 3. In round 3, all statements (42) reached a consensus and an IPE framework to guide the implementation of international electives was developed. The framework consists of three sections. Section one highlights the various IPECP competencies to be gained by learners in the areas of teamwork, interprofessional communication, roles and responsibilities of interprofessional collaborative practice, values and ethics of interprofessional collaboration, and reflection and evaluation of oneself and the team. Section two gives guidance on the structuring of the IPE international electives in health professional training institutions. This includes subsections on operational/institutional needs, acculturation considerations, teaching strategies, assessment strategies, mode of delivery, and public health considerations. Section three consists of the various practical guides and approaches that health professional training institutions could use according to what works best in their setting.The modified Delphi technique was an adequate approach to aid the development of an IPE framework to guide implementation during international electives in various health professional training institutions.